Population development in a prosperous region: Immigration and ageing in the stuttgart region - Plahuta, Simone (Raumforschung und Raumordnung | Spatial Research and Planning, 2004)
The prosperous Stuttgart Region has had a comparable positive population development in the past due to migration and birth surpluses. On the one hand the migration of young German and particularly foreign population has led to a positive natural balance and therefore to a relative advantageous demographical position against the background of an ageing society. On the other hand the proportion of often lowly qualified foreigners rose to nearly 17 percent. The following article describes the specific population development in the Stuttgart Region in the past and the forecasted progression, considering the aspects of immigration, ageing and social integration.